The rhetoric of Aristotle - Gómez Navarro, Ángel (2017)
The present text develops the meaning and sense of rhetoric in Aristotelian thought as a response to Platonic criticism and its relation to dialectic, showing that rhetorical knowledge is different from axiomatic knowledge, but that both must be recognized as complementary.